O32 Simulated patients in assessment: rationale, scope, responsibilities and ethical considerations. (31st December 2017) - Gough, S; Wilkinson, I; Hamilton, C; Greene, L
Abstract : Background: Simulated patients (SPs) are people trained to consistently portray a patient or other individual in a scripted scenario for the purposes of instruction, practice, or evaluation. SPs may also participate in teaching and assessment and provide feedback to learners. They have particular value in providing feedback on issues related to patient-centeredness. SPs can be trained to standardise their performance, to provide a consistent and accurate presentation over time and between learners. SPs offer the human element in examination questions for performance-based assessments (Nestel & Bearman, 2015). They act as a proxy for real patients; representing the patient, rather than clinician perspectives. By involving SPs in assessments, examiners have the opportunity to offer realistic, patient-centred experiences to learners. Embedding SPs in assessments contributes positively to the development of safe, patient-centred healthcare practice (Nestel & Bearman, 2015). Aim: To provide information for Educators and Trainers to optimise the involvement of SPs within formative and summative performance-related assessments. Session Description: This session will allow delegates to explore the rationale, scope, responsibilities and ethical considerations when involving Simulated Patients in performance-based assessments. Learning Objectives: At the end of the session, participants will have: Developed an insight into the rationale and scope of involving SPs in formative and summative assessments. Considered the responsibilities, requirements and expectations of both SPs and Educators/Trainers involved in assessments. Gained an awareness of the ethical considerations of involving SPs in assessments. Reflected on the application of the session content to their own area of practice. Educational Methods: Participants will be encouraged to explore each of the session learning objectives. Case studies and videos will be used to illustrate key considerations pertaining to the rationale, scope, responsibilities and ethical considerations related to adult and children SPs involved in assessments. The session will conclude with an introduction the structured SP Common Framework and Checklist (Gough et al., 2015), which can be used for guidance when involving SPs in participants' own practice. References: . Nestel D, Bearman M. Chapter 1: Introduction to simulated patient methodology. In D Nestel, M Bearman (Eds.), Simulated patient methodology theory, evidence and practice 2015:pp. 1–4. West Sussex: Wiley Blackwell. . Gough S, Greene L, Nestel D, Hellaby M, MacKinnon R, Natali A, Roberts S, Tuttle N, Webster B. Simulated patients : A standardised, quality assured approach to training and implementation (Final Project Report) 2015. Manchester: Health Education North West.